2007
DOI: 10.1152/ajpcell.00384.2006
|View full text |Cite
|
Sign up to set email alerts
|

The actin cytoskeleton regulates exocytosis of all neutrophil granule subsets

Abstract: A comprehensive analysis of the role of the actin cytoskeleton in exocytosis of the four different neutrophil granule subsets had not been performed previously. Immunoblot analysis showed that, compared with plasma membrane, there was less actin associated with secretory vesicles (SV, 75%), gelatinase granules (GG, 40%), specific granules (SG, 10%), and azurophil granules (AG, 5%). Exocytosis of SV, SG, and AG was measured as increased plasma membrane expression of CD35, CD66b, and CD63, respectively, with flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(122 citation statements)
references
References 49 publications
6
115
0
1
Order By: Relevance
“…Cytochalasin B and similar compounds disrupt the actin cytoskeleton, facilitating the release of cytoplasmic granules. Much like our results, the in vitro release of azurophilic granules that contain ␣-defensins from fMLP-stimulated PMN require the presence of an actin cytoskeleton-disrupting agent (47). Therefore, the question that arises is what could substitute for cytochalasin B priming in the in vivo setting?…”
Section: Discussionsupporting
confidence: 61%
“…Cytochalasin B and similar compounds disrupt the actin cytoskeleton, facilitating the release of cytoplasmic granules. Much like our results, the in vitro release of azurophilic granules that contain ␣-defensins from fMLP-stimulated PMN require the presence of an actin cytoskeleton-disrupting agent (47). Therefore, the question that arises is what could substitute for cytochalasin B priming in the in vivo setting?…”
Section: Discussionsupporting
confidence: 61%
“…The mechanisms involved in neutrophil degranulation are dependent on several factors such as the PKC activation pathway, intracellular Ca 2+ and the actin cytoskeleton. Jog et al (36) reported that the actin cytoskeleton restricts azurophil granule access to the plasma membrane under both basal and stimulated conditions to prevent the release of destructive enzymes such as myeloperoxidase. Studies have reported that some polyphenolic compounds, such as flavonoids, may disturb the degranulation process of the phagocytic cell by interacting with receptors on the cell membrane (37), inhibiting intracellular Ca 2+ elevation via a reduction in phospholipase-C activity (1,3) and by inhibiting PKC (by blocking the ATP binding site on the catalytic unit of PKC, for example) (13,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism by which cytohesin-1 regulates granule secretion remains to be studied, but a potential explanation may be provided by inhibition of the production of fusogenic lipids, such as PLD-derived PA (77) and/or the remodeling of the actin cytoskeleton (61). Indeed, the actin cytoskeleton regulates the secretion of several PMN granules (78), and a direct association of cytohesin-1 with the actin cytoskeleton has already been reported (54).…”
Section: Discussionmentioning
confidence: 99%